Atalik in Peoples of Dagestan in 19th - early 20th Centuries: Forms and Local Features - M. B. Gimbatova; M. K. Musaeva (Научный диалог, 2018)
One of the ancient institutionalized customs of the peoples of the Caucasus and Dagestan - atalik - is considered. The role and place of atalik in the system of social relations between the peoples of Dagestan and the North Caucasus is shown. Based on the analysis of presented material the classification of the forms of atalik is given and its zonal peculiarities in the peoples of Dagestan are marked. Simple and classic forms of atalik are revealed, which were practiced by certain peoples and served the creation of artificial kinship. It is noted that simple forms include breastfeeding up to 40 days, complex forms include education. Special attention is paid to the relationship between atalik, his family and fosterling, methods of education. It is stated that institute of atalik, emerged in antiquity and widely spread among the feudal world, played an important role in strengthening inter-society relations, cessation of blood feud and estates conflicts, expansion of symbolic boundaries of the ethnic group. Against the background of globalization processes, when ethnic features of peoples with vivid ethnospecifics are erased, the study of the features of public institutions, which once played an important role in the preservation of ethnic identity, is of great scientific and practical importance. The relevance of this study is determined by the interest in some social institutions, one of which is the atalik institute, which served as a guarantor of stability and interfaith harmony in the Caucasus.